Epidemiological Manifestation of Combined Natural Foci of Tularemia, Leptospirosis and Hemorrhagic Fever with Renal Syndrome: Mixed Infections - T. N. Demidova; N. E. Sharapova; V. V. Gorshenko; T. V. Mikhailova; A. S. Semihin; A. E. Ivanova (Эпидемиология и вакцинопрофилактика)
Relevance. Currently, the study of the combination of natural foci of zoonotic infections has become one of the urgent problems in the field of human infectious pathology, since there is a real possibility of simultaneous or not simultaneous infection of people with two or more natural focal pathogens of different etiologies and the formation of mixed infections in them. Combined lesions are characterized by territorial and morphological structure of the landscape, the presence of common reservoir hosts and types of circulating pathogens (bakterialno-bacterial, bacterial-viral, bacterial, viral, parasitic, etc.). Aims. Conduct an analysis of epizootic and epidemic activity of natural foci of tularemia, leptospirosis and hemorrhagic fever with renal syndrome (HFRS) and identify the reasons for the occurrence of mixed infections in humans. Materials and methods. To assess the activity of natural foci and to identify epizootics in populations of mouse-like rodents, the materials of long-term epizootological studies in Russia were used. A comprehensive study of rodents captured in the natural foci of the Central Federal District and the Northwestern Federal District for tularemia by serological, molecular genetic and biological methods was carried out. Statistical data on the incidence of tularemia, leptospirosis and HFRS in the territory of the Russian Federation for 2015-2020 are presented. Results. The analysis of our own research and literature data allowed us to characterize the combined foci of tularemia, leptospirosis and HFRS as bacterial-viral, according to the degree of combination in the parasitic system of common reservoir hosts, such as common, red, water voles, forest, field and house mice, insectivores. According to the level of combination of the morphological structure of the landscape, the foci belong to steppe, meadow-field, forest and floodplain-swamp, and by type these foci are characterized as infectious geographically combined. The assessment of the epizootic manifestation of foci is determined by the number of natural carriers of infections, isolation of cultures of pathogens, detection of antigen, antibodies or DNA from environmental objects, as well as the recorded incidence of people. The intensity of the circulation of infectious agents in natural foci varies in time and space depending on biotic (number of carriers, abundance of vectors, etc.) and abiotic (temperature, humidity, etc.) environmental factors. Adverse weather conditions (frosts, thaws, etc.), lack of food supply force wild rodents to migrate to populated areas, creating additional risks of human infection. To assess the epizootic manifestation of foci, the volumes of epizootic studies are of great importance, which have been reduced to a minimum and according to their results it is impossible to predict the epidemic manifestation of a particular focal area. The incidence of tularemia, leptospirosis and HFRS in humans depends on the characteristics of human-animal contacts. The epizootological situation and nosological profile in different regions have significant differences, which determines the difference in the risk of human diseases. In recent years, the number of officially registered patients with tularemia and leptospirosis in the Russian Federation is relatively small and ranges from several tens to hundreds of cases. However, the figures of officially registered patients do not reflect the real picture of the incidence of these infections, and to a greater extent indicates not the wellbeing of these nosoforms, but rather the problems of identifying (diagnosing) sick people of a particular infection. The analysis of the incidence of each case of tularemia over the past ten years has allowed to identify mixed-infected patients with pathogens of zoonotic natural focal infections. These are mainly patients with moderate-severe and severe manifestations of the disease with a primary diagnosis (acute respiratory infections, acute respiratory viral infections, purulent lymphadenitis of various localization, angina, chronic pyelonephritis, pneumonia, hepatitis, etc.). Diagnostics is aimed at determining the nosology, clinical form, severity of the condition, detection of complications and indications for treatment. For natural focal infections, information on epizootic and epidemiological examination of the focus of an infectious disease is necessary. The diagnosis is established on the basis of clinical and epidemiological data: a combination of fever and intoxication, determine the relationship of the development of the disease with work and the circumstances in which the patient was. Currently, as a result of the examination of sick people, mixed infections with natural focal infections are increasingly being registered: HFRS + tularemia; tularemia+ leptospirosis; leptospirosis + HFRS; tularemia+ borrelliosis; rickettsiosis +tularemia, etc., the presence of two pathogens of zoonotic infections was detected in the patient during successive studies. It was found that the infection of people occurred in areas enzootic for these infections. It should be remembered that a high-quality comprehensive epizootological examination of focal areas allows you to make a forecast and determine the factors of real epidemiological risk. Conclusions. In the epidemiology of any natural focal disease, it is necessary to take into account the presence of combined foci in a particular territory. Lack of experience in the diagnosis of natural focal infections of tularemia, leptospirosis and HFRS often leads to diagnostic errors, and the lack of alertness to their appearance makes it difficult to identify sporadic cases of diseases. Most nosoforms of hemorrhagic fevers lack specific prevention (HFRS among them), therefore it is necessary to strengthen measures aimed at improving the focal areas, i.e. to carry out deratization work in the most active foci near settlements and mass recreation areas of the population. Mixed infection can lead to both activation and suppression of the protective mechanisms of the human body. The exchange of information between medical and veterinary services will make it possible to better organize and carry out comprehensive measures for epizootic and epidemiological surveillance on the territory of natural foci of zoonotic infections. The formation of modern tactics of differential laboratory diagnostics will ensure the identification of mixed-infected patients with natural focal infections.